Chiral Fibers Formation Upon Assembly of Tetraphenylalanine Peptide Conjugated to a PNA Dimer. Issue 37 (23rd May 2022) - Mosseri, Andrea; Sancho‐Albero, Maria; Leone, Marilisa; Nava, Donatella; Secundo, Francesco; Maggioni, Daniela; De Cola, Luisa; Romanelli, Alessandra
Abstract: Self‐assembly of biomolecules such as peptides, nucleic acids or their analogues affords supramolecular objects, exhibiting structures and physical properties dependent on the amino‐acid or nucleobase composition. Conjugation of the peptide diphenylalanine (FF) to peptide nucleic acids triggers formation of self‐assembled structures, mainly stabilized by interactions between FF. In this work we report formation of homogeneous chiral fibers upon self‐assembly of the hybrid composed of the tetraphenylalanine peptide (4F) conjugated to the PNA dimer adenine‐thymine (at). In this case nucleobases seem to play a key role in determining the morphology and chirality of the fibers. When the PNA "at" is replaced by guanine‐cytosine dimer "gc", disordered structures are observed. Spectroscopic characterization of the self‐assembled hybrids, along with AFM and SEM studies is reported. Finally, a structural model consistent with the experimental evidence has also been obtained, showing how the building blocks of 4Fat arrange to give helical fibers. Abstract : Tetraphenylalanine peptide (4F) conjugated to the PNA dimer "at" self‐assembles to produce helical fibers. Interactions between both components of the conjugate, either the peptide and the nucleobases, trigger self‐assembly. Antiparallel beta sheets between the peptides are zipped by hydrogen bonds between complementary nucleobases. Spectroscopic measurements, microscopy data along with a computational model support this hypothesis. On the contrary, when "at" is replaced by "gc" PNA, odd shaped spheroid are obtained.